Diabetes in dental practice - review of literature - Mateusz Jan Baranowski; Agnieszka Wójtowicz; Joanna Wysokińska-Miszczuk; Justyna Klempka; Michał Kubiszyn (Kazimierz Wielki University, 2019)
Introduction: Diabetes belongs to the group of metabolic disorders and is characterized by chronic hyperglycemia resulting from abnormal secretion of insulin and / or tissue resistance to its action. The association of elevated glycemia with periodontal disease and oral cavity is clear and proven in many scientific publications. Purpose of work: The aim of the study was to characterize the oral cavity of a patient with diabetes, its diagnosis and treatment based on a review of English-language literature from 2014-2018, and an attempt to answer some questions and problems raised by practicing physicians who want to effectively help those who report to them patients with the above disease. Material and methods: The PubMed database was analyzed using the keywords: "diabetes", "diabetes periodontitis", "diabetes oral health", "diabetes dental treatment". 23 English-language works were qualified for the review. Results: the patient with diabetes should be made aware by the dentist, understand the impact of his disease on the body, especially the tissues of the parodontium and the oral mucosa, regularly report on the check-up visit Summary: The dentist is the first to see signs of failure to diagnose chronic hyperglycaemia. He should be vigilant, because such persons are patients at high risk of complications after dental treatment. The basis for maintaining oral health is, above all, the permanent maintenance of impeccable, basic oral hygiene.